Cornerstones: Shaligrams as Kin - Walters, Holly ca. 20./21. Jh. (The journal of religion, 2022)
Shaligrams are the sacred fossil ammonites of the Himalayas. Viewed primarily as manifestations of Hindu gods, these aniconic deities are obtained by pilgrimage to Himalayan Nepal and are then brought home, to families and communities all over South Asia and the diaspora, to become both deity and kin. Shaligrams also act as conversants, if inanimate ones, during the course of ritual and everyday talk. Therefore, the semiotic separation of bodies and persons in Shaligram religious practice, discussed here in relation to Tulsi Vivah (the marriage of Tulsi and Shaligram) festivals and in daily puja and darshan rituals, reimagines individuals as represented by but distinct from their physical forms. This practice then links language and ritual objects with broader understandings of human and divine personhood in South Asia as it is conceptualized both within and between physical bodies.